Epistemologi Ekonomi Islam: Integrasi Al-Qur'an, Sunnah, Ijma', dan Qiyas dalam Pembangunan Ekonomi Syariah - Arofiani Mutmainah; Dina Cheetah Khairiyah; Habibah Ramadhani Nasution; Ahmad Wahyudi Zein (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to explore how the integration of the Qur'an, Sunnah, Ijma', and Qiyas becomes the main foundation in building a sharia economic framework that is relevant to modern challenges. The Qur'an, as the main source of Islamic law, provides holistic and transformative guidelines, while the Sunnah serves as an explanation and reinforcement of the principles contained in the Qur'an. On the other hand, Ijma' and Qiyas play a crucial role in formulating new laws that are not explicitly mentioned in the sacred texts, thus enabling the application of sharia in the context of contemporary economic problems that continue to develop. This study uses a literature study approach to analyze various theoretical and empirical perspectives related to the application of the four sources of law in sharia economics. The research findings show that the integration of the four sources of Islamic law not only forms a strong normative basis but also provides an understanding in responding to the needs of modern society. In this way, sharia economics can accommodate the principles of justice, poverty, and inclusiveness, which are the essence of building an economic system oriented towards collective welfare. In addition, this study critiques the challenges in implementing sharia principles, especially in the process of interpretation and adaptation to global dynamics. The limitations of conventional methodologies in integrating legal sources often become obstacles in creating solutions that are appropriate to local and global contexts. Therefore, this study suggests the need for a multidisciplinary approach involving collaboration between scholars, economists, and policy makers to ensure that sharia economics can develop consistently and relevantly to the needs of the times. These findings not only enrich academic discourse but also provide practical contributions in efforts to build a more just, sustainable, and Islamic-value-based economic order.